RANCANGAN SISTEM INFORMASI PERPUSTAKAAN DIGITAL PERGURUAN TINGGI (STUDI KASUS : PERPUSTAKAAN AKBID AISYIYAH PONTIANAK) - Agung Sasongko (Universitas Bina Sarana Informatika, 2015)
Libraries are regular facilities provided by the college as a means of supporting add insight and knowledge for all academic faculty. Library services in the digital information age of today's demanding provide services mainly in terms of speed of information availability and information collection owned by the existing book collection details. Akbid Aisyiyah Pontianak today still use manual way to serve the activities of the library. Currently they are working to provide better library services by utilizing information technology, how to implement the sistem at the library information services. This study aimed at to provide proper sistem design for use in library Aisyiyah Pontianak Akbid fit their needs. In conducting this study the authors used the software developing a method of SDLC (Software Development Life Cycle), because this method is considered appropriate to solve the problems of their sistem development. The output of this research is the design of the library information sistem that can be used by the university.Keyword: Digital Library, Information System, SDLC